2022
DOI: 10.1111/jfpe.14042
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling and kinetic behavior of Indian Umblachery cow butter and its nutritional degradation analysis under modified atmospheric packaging technique

Abstract: Main objective of the study is to evaluate the effect of polyphenols enrichment, modified atmosphere packaging (CO2: 20%, N2: 75%, O2: 5%) and storage time on the shelf‐life solidity and nutritional degradation of butter from Indian native breed of Umblachery cow. The butter samples were incorporated and enriched with polyphenols and flavonoids from the seed coat extracts of Cajanus cajan (136.5 mg of gallic acid equivalents/g and 68.7 mg of quercetin equivalents/g) and butylated hydroxyl anisole (200 ppm) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…a Linear regression equation of first-order reaction kinetics.Figure2α-tocopherol and g-i: β-Carotene) in fresh lactic butter samples (CB: Control butter, MCEOsB: M. communis EOs butter, APB: Ascorbyl palmitate butter).found to be either lower or similar to this study(Piedrahita et al 2015;Basheer and Muthusamy 2022).Darmawan et al (2023) found that lignin increased reaction rates and Q 10 values in tengkawang butter.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…a Linear regression equation of first-order reaction kinetics.Figure2α-tocopherol and g-i: β-Carotene) in fresh lactic butter samples (CB: Control butter, MCEOsB: M. communis EOs butter, APB: Ascorbyl palmitate butter).found to be either lower or similar to this study(Piedrahita et al 2015;Basheer and Muthusamy 2022).Darmawan et al (2023) found that lignin increased reaction rates and Q 10 values in tengkawang butter.…”
supporting
confidence: 71%
“…It is a popular soured Turkish dairy product. Cream processing and storage conditions significantly affect the oxidative stability of butter (Khan et al 2019;Basheer and Muthusamy 2022). The peroxide value (PV) is used to determine oxidation status, while thiobarbituric acid reactive substances (TBARs) is a useful parameter to estimate secondary oxidation products in dairy products (Khan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peroxide values of the MAP1 and MAP2 samples increased rapidly on day 21. At the end of storage, the peroxide values began to decrease as secondary products are formed from the products of the first oxidation during the second phase of lipid oxidation [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Для обобщенной оценки влияния факторов на скорость окисления липидов исследователи использовали кинетическую модель Аррениуса (зависимость скорости химической реакции от температуры), с помощью которой рассчитывали изменение энергии активации сливочного масла. ЭОС значительно снизил образование продуктов окисления, потеря полифенолов к концу шестого месяца хранения составила 21-36 % при 4 °C и 31-55 % при 25 °C с и без модифицированной атмосферной упаковки соответственно[28].Mikdame H и соавторы использовали отходы производства оливкового масла (вода, использованная в процессе извлечения масла из оливок, и жмых) как источник полифенолов. Включение экстракта жмыха или концентрированной технической воды снижало кислотное и перекисное число масла, снижало микробиологическую обсемененность относительно контроля после 60 суток хранения при температуре 25 °С[29].выводы Продовольственные потери -одна из важнейших проблем, стоящих сегодня перед пищевой индустрией в современном мире.…”
unclassified